Optimalisasi Biaya Distribusi Pupuk PT Ngadi Makmur dengan Metode Transportasi - Eka Febriyanti, Nuraini; Dwi Linggarani P., Laras; Setyaningsih, Desi; Kusumaning Putri, Aprilia; Purwaningrum, Titis (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Distribution is a crucial component of a company’s operations that significantly impacts total costs. PT Ngadi Makmur, a company engaged in fertilizer distribution, faces challenges in optimizing distribution costs to enhance efficiency and competitiveness. This study aims to optimize fertilizer distribution costs using the North West Corner (NWC) transportation method. The method is chosen for its simplicity in providing an efficient initial solution for distribution problems. The research utilizes fertilizer distribution data from PT Ngadi Makmur, including transportation costs, shipment quantities, and demand at each destination. The analysis is conducted by applying the NWC method to obtain an initial solution, further refined using the stepping stone method to achieve optimal results. The findings reveal that the NWC method provides an initial solution close to optimal, resulting in a 12% reduction in distribution costs compared to the company’s previous traditional methods. This optimization not only reduces operational expenses but also enhances the speed and accuracy of deliveries. The study recommends implementing other, more advanced transportation methods, such as the Vogel method, for further development. Through this optimization, PT Ngadi Makmur can improve efficiency and support sustainable business practices in the competitive fertilizer market.